SPE Middle East Oil &Amp; Gas Show and Conference 2015
DOI: 10.2118/172744-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gas Adsorption and Composition on Unconventional Shale Permeability Measurement

Abstract: Permeability determination of organic-rich shales is still a major challenge. Uncertainty in this estimate involves several factors. Two significant ones are the occurrence of gas adsorption which can severely limit gas transport in the pores and understanding the physical chemistry issues of the pore's surface area estimation when using various gases. In this study, we reported our experimental results of permeability measurement on several unconventional shale samples, and investigated the effect of gas type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Several correlations were proposed for b in Eq. 5 on the basis of laboratory experiments (Heid et al 1950;Jones and Owens 1980;Sampath and Keighin 1982;Florence et al 2007;Tanikawa and Shimamoto 2009); b is generally taken to be a function of absolute permeability (and in some cases, of porosity) and, to a lesser extent, of gas type. Throughout the literature, there is evidence of deviations from Eq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several correlations were proposed for b in Eq. 5 on the basis of laboratory experiments (Heid et al 1950;Jones and Owens 1980;Sampath and Keighin 1982;Florence et al 2007;Tanikawa and Shimamoto 2009); b is generally taken to be a function of absolute permeability (and in some cases, of porosity) and, to a lesser extent, of gas type. Throughout the literature, there is evidence of deviations from Eq.…”
Section: Introductionmentioning
confidence: 99%
“…5 (Klinkenberg 1941;Jones and Owens 1980;Sampath and Keighin 1982;Noman and Kalam 1990;Wu et al 1998;Rushing et al 2004;Li et al 2009;Macini et al 2011;Fathi et al 2012;Dong et al 2012), with most reporting a deviation from the Klinkenberg straight-line plot, especially in low-permeability cores. Jones and Owens (1980) conducted a series of experiments on low-permeability gas sands. Even though their results yielded reasonably straight lines in Klinkenberg plots, they noticed an overestimation of absolute permeability of up to 25%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another essential influence on permeability evolution of sorbing porous media, such as shale and coal rocks, comes from sorptioninduced volumetric strains. 30 Jin et al 31 measured shale permeability by using different gas types and reported that the nitrogen permeability is higher than the argon permeability due to their different adsorption potentials. Argon's sorption potential is larger than that of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to CO 2 , this two‐stage evolution of permeability with gas pressure was consistently observed for N 2 . Jin et al 16 measured the change of permeability of N 2 and Ar in North America shale during gas desorption. The permeability was measured under a CCP of 11 MPa while the gas pressure decreased from 9 to 4 MPa.…”
Section: Introductionmentioning
confidence: 99%